Employees’ mental wellbeing, organizational outcome and innovative practices during covid-19 - DR. GIGI G.S,; MS. PAVITHRA.R, (The journal of contemporary issues in business and government, 2020)
This study is conducted to analyze mental wellbeing of employees’ and its organizational outcome during COVID-19. Due to this global pandemic, the Nation’s economy has declined and hence many organizations decided to cut down the cost by lowering the salary package and to terminate few employees. Organization shifted to remote working but this caused a negative impact on employees’ mental health. Employees are stressed due to workload, lack of communication, work life balance, insecurity of job, anxiety and other reasons during COVID-19. The dependent factor called organizational outcome is influenced by the factors namely employee wellbeing, virtual communication, organizational support and social media. The researcher circulated questionnaires among Information technology (IT) industry employees. The sample size of the study is 90. Various analytical tools such as frequency analysis, mean analysis, T- Test, ANOVA and Regression for comparing the dependent and independent factor have been analyzed using SPSS software in order to analyze the primary data. From the results, It is inferred that the organisation's support is the most influencing factor. Providing mental wellbeing training and programs, implementing new policies which help in bringing positive impact on employees and their performance which results in effective organization outcome.